School factors and academic achievement of primary students in Dujiangyan, China: psychological capital as a mediator - Ma, Yuwei; Ooi, Boon Keat (Frontiers in Education, 2025)
School factors represent a significant variable that exerts a profound influence on student academic achievement (AA). The construction and development of psychological capital (PsyCap) theory has led to the realization that PsyCap is an important factor influencing student AA. This study aimed to investigate the effect of non-physical school factors, namely school satisfaction (SS), teacher support (TS) and teacher-student relationship (TSR), on student AA through their PsyCap. Adopting a quantitative research methodology based on positivist research concepts, the study analyzed the data using SPSS 27 and Amos 27. The findings indicated that SS, TS, TSR, and PsyCap exerted a considerable positive influence on student AA. The effect sizes were as follows: SE(SS → AA) = 0.258***, SE(TS → AA) = 0.233***, SE(TSR → AA) = 0.255***, and SE(PsyCap→AA) = 0.427***. The results demonstrated a significant mediating effect of PsyCap on the effects of SS, TS, and TSR on student AA. The mediating effect accounted for 29.1, 41.2, and 37.2% of the total effect of each pathway, in that order. A noteworthy finding of this study is that the key influencers, person, exerts a more pronounced effect on students’ PsyCap than other influencers. Furthermore, the impact of PsyCap on student AA is also more pronounced. The research model developed in this study on the influence of SS, TS and TSR on student AA through the mediation of PsyCap addresses a gap in the existing educational research literature and contributes to the evolving body of knowledge on PsyCap in the field of education, particularly in the context of primary education.